Reduction of Air Pollutants of Urban Canyons through Management of Particulate Matters 2.5 in the Streets - Rishabh Anand (International Journal of Environmental Noise and Pollution Control, 2025)
Urban canyons are long and high sky-scrappers closely to narrow streets result in very different microclimate challenges. These spaces often trap pollutants and restrict air circulation and intensify more retention of heat making them very uncomfortable for pedestrians. In order to resolve this issue a strong set of design guidelines and frameworks were needed which can balance out the human comfort and environmental aspects. This research studies strategies to improve micro climate in canyons via integrating green infrastructure to optimize circulation of air while selecting materials enhancing quality of air and comfort from temperature. A case study is highlighted in the project in downtown Toronto applying the proposed design framework with tree placement, green walls and reflective or permeable materials. To assess the impact of these interventions micro-climatic simulations were performed that investigate changes in concentration of air pollutants, circulation of air and temperature regulation. Research findings show that strategic placement of vegetation improves quality of air by capturing particulates and reducing emission of carbon. Careful material choice helps decrease extremes of heat while enhancing circulation reduces discomfort from stagnant air. Results show that approach based on integration of vegetation and material selection coupled with optimization of air circulation produces a more breathable air and comfort. Benefits go beyond environmental sustainability; they also promote social engagement because urban spaces become more inviting and attractive. Cooling benefits enhanced air circulation contribute to reduction of urban heat islands thereby making cities more resilient to climate change. This study emphasises significance of a design approach based on data as well as prioritizing people. Success with use of interventions serves as benefit further for urban design, landscape design as well as urban planning and sustains further future urban development in high density areas. Rise of urban population hence matters greatly ensuring that density areas remains sustainable, functional and hospitable as we look to future urban development.
Keywords: Urban canyons; pedestrian comfort; pollutants reduction; street design; urban design